THE ROLE OF THE CONCEPT OF INFORMATION WARS IN THE MODERN PERIOD OF IDEOLOGICAL PROCESSES - Xujanova Tamara Juraevna (Academia Science Repository, 2023)
This article explores the role of the concept of information wars in shaping ideological processes in the modern era. It delves into the ways in which information wars are utilized to manipulate, influence, and shape ideologies in the digital age. Drawing upon interdisciplinary perspectives and research, the article examines the impact of information warfare strategies on the formation, dissemination, and polarization of ideologies. It analyzes the complex interplay between information warfare, digital media, and ideological dynamics, considering the implications for societal cohesion, political discourse, and public opinion. By shedding light on the multifaceted relationship between information wars and ideological processes, this article provides insights into the challenges and opportunities presented in the contemporary information landscape [1].